Luseogliflozin inhibits high glucose-induced TGF-2 expression in mouse cardiomyocytes by suppressing NHE-1 activity - Naoya Osaka; Yusaku Mori; Michishige Terasaki; Munenori Hiromura; Tomomi Saito; Hironori Yashima; Yoshie Shiraga; Raichi Kawakami; Makoto Ohara; Tomoyasu Fukui; Sho-ichi Yamagishi (Journal of International Medical Research, 2022)
Objective Sodium-glucose cotransporter-2 (SGLT2) inhibitors exhibit cardioprotective properties in patients with diabetes. However, SGLT2 is not expressed in the heart, and the underlying molecular mechanisms are not fully understood. We investigated whether the SGLT2 inhibitor luseogliflozin exerts beneficial effects on high glucose-exposed cardiomyocytes via the suppression of sodium-hydrogen exchanger-1 (NHE-1) activity. Methods Mouse cardiomyocytes were incubated under normal or high glucose conditions with vehicle, luseogliflozin, or the NHE-1 inhibitor cariporide. NHE-1 activity and gene expression were evaluated by the SNARF assay and real-time reverse transcription-polymerase chain reaction (RT-PCR) analysis, respectively. Six-week-old male db/db mice were treated with vehicle or luseogliflozin for 6 weeks, and the hearts were collected for histological, RT-PCR, and western blot analyses. Results High glucose increased NHE-1 activity and transforming growth factor (Tgf )-β 2 mRNA levels in cardiomyocytes, both of which were inhibited by luseogliflozin or cariporide, whereas their combination showed no additive suppression of Tgf -β2 mRNA levels. Luseogliflozin attenuated cardiac hypertrophy and fibrosis in db/db mice in association with decreased mRNA and protein levels of TGF-β2. Conclusions Luseogliflozin may suppress cardiac hypertrophy in diabetes by reducing Tgf -β2 expression in cardiomyocytes via the suppression of NHE-1 activity.